2010
DOI: 10.1096/fj.10-167049
|View full text |Cite
|
Sign up to set email alerts
|

IRF2BP2 is a skeletal and cardiac muscle-enriched ischemia-inducible activator of VEGFA expression

Abstract: We sought to identify an essential component of the TEAD4/VGLL4 transcription factor complex that controls vascular endothelial growth factor A (VEGFA) expression in muscle. A yeast 2-hybrid screen was used to clone a novel component of the TEAD4 complex from a human heart cDNA library. We identified interferon response factor 2 binding protein 2 (IRF2BP2) and confirmed its presence in the TEAD4/VGLL4 complex in vivo by coimmunoprecipitation and mammalian 2-hybrid assays. Coexpression of IRF2BP2 with TEAD4/VGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 48 publications
4
61
0
Order By: Relevance
“…We have not found DIF-1 to act as an activator in the various breast and nonbreast cell lines under the conditions we studied. However, it is of interest that Teng et al (32) reported that cardiac muscle contains very high levels of IRF-2BP2 protein compared with other tissues. The level of IRF-2BP2 protein in muscle is further increased in ischemia and was reported to stimulate expression of vascular endothelial growth factor A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not found DIF-1 to act as an activator in the various breast and nonbreast cell lines under the conditions we studied. However, it is of interest that Teng et al (32) reported that cardiac muscle contains very high levels of IRF-2BP2 protein compared with other tissues. The level of IRF-2BP2 protein in muscle is further increased in ischemia and was reported to stimulate expression of vascular endothelial growth factor A.…”
Section: Discussionmentioning
confidence: 99%
“…The level of IRF-2BP2 protein in muscle is further increased in ischemia and was reported to stimulate expression of vascular endothelial growth factor A. This apparently occurs through the interaction of IRF-2BP2 in cardiac cells with the TEA domain transcription factor TEAD4 and VGLL4, a member of the vestigial-like family or regulators (32). Thus, like other transcription factors (e.g., nuclear hormone receptors), IRF-2BP2 may have the potential to act as a repressor or activator, depending on the cell and possibly promoter context.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Exposure of macrophages to bacterial lipopolysaccharide activates the M1 inflammatory phenotype, whereas exposure to interleukin (IL)-4 favors the M2 anti-inflammatory phenotype. 13 In human monocyte-derived macrophages, IRF2BP2 mRNA levels are elevated in the M2 state, but are suppressed to nearly undetectable levels in the M1 state 14 (Geoprofiles, GDS2430:224570_s_at), suggesting that IRF2BP2 may be involved in macrophage polarization.…”
Section: Irf2bp2 Reduces Macrophage Inflammation and Susceptibility Tmentioning
confidence: 99%
“…19 A custom rabbit antibody against IRF2BP2 was described. 12 Cryostat sections (10 μm) were subjected to immunofluorescence, TUNEL (Promega, G3250), hematoxylin and eosin (PerkinElmer), and oil red O staining. Primary antibodies to KLF2 (Millipore), mouse ApoB (gift of Dr Ross Milne of the University of Ottawa Heart Institute), Casp3 (Cell Signaling), ApoA1, ApoE, F4/80, iNOS, Arg1, Retnlb, H3K4me3, and GAPDH (Abcam), Ki67, MT-CO2, CD3, CD68, CD206 (Santa Cruz), CD11b (AbD Serotec), and actin (Sigma) were used.…”
Section: Antibodies For Immunoblot Immunofluorescence and Chromatinmentioning
confidence: 99%
See 1 more Smart Citation